2008
DOI: 10.1080/13880200802215768
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Hepatoprotective Effects ofPhysalis peruvianaExtract against Acetaminophen-Induced Liver Injury in Rats

Abstract: The aim of this study was to examine the antioxidant activities of Physalis peruviana L. (Solanaceae) aqueous extract (PPWE) and its protective effect against acetaminophen (APAP)-induced hepatotoxicity in rats. Using different models of antioxidant assay, namely ferric thiocyanate, 2,2-diphenyl-1-picrylhydrazyl (DPPH), and reducing power, PPWE showed a dose-dependent increase in antioxidant activities, with total antioxidant activity (IC 50 : 0.81 µg/ml) close to that of vitamin C (IC 50 : 0.89 µg/ml). APAP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 39 publications
3
27
2
6
Order By: Relevance
“…Demir et al [7] also found similar results that the antioxidant activity of P. peruviana fruit, from a local supplier from Antalya, using the DPPH radical scavenging method determined the IC 50 values of ascorbic acid and P. peruviana were calculated as 1.06 µg/ml and 430 µg/ml, respectively. Chang et al [8] suggest that the aqueous extract of P. peruviana has antioxidant activity in a concentration-dependent manner. When compared with vitamin C (for the 5 µg/ml, scavenging 94.64 %), their extract concentrations 50 µg/ml, 100 µg/ml, and 300 µg/ml showed the scavenging 13.17 %, 22.04 %, 52.72 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demir et al [7] also found similar results that the antioxidant activity of P. peruviana fruit, from a local supplier from Antalya, using the DPPH radical scavenging method determined the IC 50 values of ascorbic acid and P. peruviana were calculated as 1.06 µg/ml and 430 µg/ml, respectively. Chang et al [8] suggest that the aqueous extract of P. peruviana has antioxidant activity in a concentration-dependent manner. When compared with vitamin C (for the 5 µg/ml, scavenging 94.64 %), their extract concentrations 50 µg/ml, 100 µg/ml, and 300 µg/ml showed the scavenging 13.17 %, 22.04 %, 52.72 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…P. peruviana is a medicinal plant widely used in folk medicine for treating diseases such as malaria, asthma, hepatitis, dermatitis, cancer, diuretic, rheumatism [3,7]. The fruit of P. peruviana may be considered as good sources of natural antioxidants for medicinal uses [8,9]. Fruits are valuable sources of nutritional elements such as magnesium (Mg), calcium (Ca), sodium (Na), potassium (K), phosphorus (P), iron (Fe), zinc (Zn) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the observed increase in alterations to liver enzymes, including ALT, AST and ALP, in HCCreceived CHJ rats may be due to the improvement of the functional status of hepatocytes with preservation of cellular architecture leakage of intracellular enzymes through membrane-stabilizing activity. [18,53] Previous studies have suggested that CGJ is a significant source of natural antioxidative compounds.…”
Section: [42]mentioning
confidence: 99%
“…[ [12][13][14] Cape gooseberry extracts show antioxidant activity, [15,16] anti-inflammatory activity, [17,18] and anti-hepatotoxic [18] and antiproliferative effects on hepatoma cells. [19] This fruit also has excellent potential as a food-based strategy for anti-diabetic and anti-hypertensive products.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies has been conducted to test health properties of Physalis peruviana L plant, cape gooseberry and calyx, concluding to a potential association of intakes with in vitro and in vivo anti-inflammatory activity [25,26], inhibition of TPA-induced (12-O-tetradecanoylphorbol-13-acetate) oedema in mice [27], effectiveness in decreasing cadmium toxicity in rats [28,8,29], hepatoprotective, renoprotective and cholesterol suppression effects [8,[30][31][32][33][34], antidiabetic and antihypertension activity [35][36][37][38][39] and cytotoxic activity against in vitro non-specific cancer cells [40] and lung cancer cells [41]. These potential health benefits are associated with the presence of phytochemicals in the extracts such as withanolides, physalins, vitamin C, flavonoids and phenolics, among others.…”
Section: Fruit and Vegetables Phytochemicals And Health Propertiesmentioning
confidence: 99%